Research on Support Type Selection of Foundation Pit of Rail Transit Station Based on Improved AHP Method - Liu, Yan; Lu, Linhai; Liu, Junyan; Zhao, Jianjun (IOP conference series. Earth and environmental science, 2020)
With the rapid development of underground space, a large number of complex foundation pit projects have emerged. It is undoubtedly an important task to select a safe, economic, scientific and reasonable support scheme and seek a scientific and reasonable optimization method of foundation pit support scheme in combination with regional characteristics. This paper tries to find a simple and practical method of scheme selection which meets people's psychological comparison scale. The traditional analytic hierarchy process (AHP) is improved, the grade of traditional evaluation index is improved, and the index scale is introduced. An analytic hierarchy process based on the seven grade index scale is put forward to make it more suitable for people's psychological comparison scale. Through consistency test, the scientificity and rationality of the improved layer analysis method are verified, and applied to the foundation pit engineering with close proximity to rail transit. Through the establishment of the tomographic structure model and judgment matrix, the calculation and optimization are carried out. It is found that the support scheme of diaphragm wall + internal support is the optimal scheme of the project. This method can provide theoretical support for the establishment of regional foundation pit support selection.